Peak Sexual and Spiritual Experience: Exploring the Mystical Relationship - MacKnee, Chuck (1996)
The nine-category phenomenological typology of mystical peak experiences proposed by Pahnke (1980) was used to construct a framework for understanding and relating peak potentials for sexuality and spirituality. Examples from mystics—St Catherine of Siena, St John of the Cross and St Teresa of Avila—demonstrate the erotic connectedness they experienced in spiritual peaks. It is proposed that integrating understanding of sexual and spiritual peak experience provides more knowledge of what it means to be ‘fully human’ and creates insight into the depths of intimacy with self, others, and the ultimate.